PENGARUH PENGENDALIAN INTERNAL, AKUNTABILITAS DAN TRANSPARANSI TERHADAP KINERJA PEMERINTAH PADA OPD KABUPATEN INDRAGIRI HILIR - RANTI MELASARI; ROSLIANA ROSLIANA; PENI SILVIONITA (JURNAL AKUNTANSI DAN KEUANGAN, 2022)
This study aims to obtain empirical evidence of the effect of internal control, accountability and transparency on government performance in the OPD of Indragiri Hilir Regency. The population in this study were all 34 OPD in Indragiri Hilir District. The method for selecting the sample used a purposive sampling method, with a total sample of 56 respondents who filled out the research questionnaire. The analysis technique used is multiple linear regression. The results of the study show that internal control affects government performance, accountability influences government performance and transparency influences government performance. Simultaneous test results show that internal control, accountability and transparency affect government performance in the OPD of Indragiri Hilir Regency